Relationship Between Integrated Marketing Communication and Brand Equity - Nadia Theodora (International Journal of Social Science and Business, 2021)
Integrated Marketing Communication (IMC) system became a warm and tangible topic in the field of marketing activities. Whereas in previous years, most marketing activities only utilize traditional advertising media, but now the situation has been different, the marketing funds owned by the company are allocated to various communication activities such as sales promotion, direct sales to consumers, branding activities, public relations, and advertising. This study will try to explain the relationship between the application of integrated marketing communication (IMC) and its influence to the establishment and development of brand equity and also will look at the role of each element of integrated marketing communication to brand equity. This article uses the literature review method by summarizing the result of various credible studies that highlight the relationship between IMC and brand equity. The result shows that there is a direct relationship between the simultaneous application of all elements of IMC to the formation of brand equity. But partially each element of IMC has its own impact on the formation of brand equity, depending on the context of the company, region, time, and target consumers. The conclusion of this research is that along with the seven elements in integrated marketing communication have an influence on the formation and development of brand equity, but partially each of these elements has their own implications for the formation of brand equity depending on the context of the company, region, time, and target consumer.